CO2 emissions during the operation of autonomous water heating systems - A. L. Toropov (Vestnik MGSU)
Introduction. CO2 emissions during the operation of heat generators of autonomous heat supply systems is one of the most important indicators of the man-made impact on the Earth’s atmosphere. Heat generation is carried out by heat pumps, gas and electric boilers, solid and liquid hydrocarbon fuel systems. The purpose of the work — Assessment of the CO2 emission indicator per kilowatt of heat energy of the specified generators of heat supply systems with real energy efficiency of heat generators of heat supply systems with radiator-type heating devices.Materials and methods. Official data of the Federal State Statistics Service of the Russian Federation, reports of the Ministry of Energy, the Ministry of Economic Development, current GOST and regulatory documents are used. Experimental data were used to calculate the energy efficiency coefficients of heat generators of autonomous heat supply systems. The calculations were carried out by methods of mathematical modelling.Results. The values of CO2 emissions per kilowatt of heat energy for autonomous water heating systems in the generation of heat energy by heat pumps (ASHP), gas condensing and convection boilers, solid and liquid fuel boilers were determined.Conclusions. The assessment of CO2 emissions of heat generators of autonomous water heat supply showed dependence on the structure of production and transportation of electric energy, climate and heating devices used. All of these parameters are different for different countries. When analyzing country-specific data, different thermal units have minimal carbon footprint.